Studies on the Protonation Constants of Some Triazoles in Ethanol-Water Mixtures - ISLAMOGLU, FATIH; KAHVECI, BAHITTIN; OZIL, MUSA; AKYUZ, EMINE (Asian Journal of Chemistry, 2010)
Several studies, involving the formation and investigation of biological activities of some triazoles derivatives. These derivatives have weak acidic properties. To gain more information about the effect of solvent on triazoles, the stoichiometric protonation constants of 17 triazoles (3 series) in ethanolwater mixtures were determined at an ionic strength of 0.10 M NaCl and at 25.0 ± 0.1 ºC under nitrogen atmosphere. A potentiometric method was used and the calculation was carried out using the PKAS computer program. The corresponding pKa values of these triazoles were determined in ethanol-water mixtures mixtures. Thus, the effects of solvent and molecular structure upon acidity were investigated. The logarithm of the protonation constants of the triazoles decreased linearly with increasing ethanol content. The variation of these constants is discussed on the basis of specific solute-solvent interactions.